Impact of Covid-19 on Business Performance: A Case Study of Starbucks - Sinha, Rupesh; Ganatra, Varsha; Pandey, Priya; Arumugan, Deepaa Darshanie Lim A/P; Kee, Daisy Mui Hung; Lekha, Gopalam Sree; Kumar, Navaneetha; Kew, Sin Dee; Dhupad, Asha; Nair, Rajesh Kumar; Tenh, Ying Ying; Yue, Haoran (AIBPM Publisher, 2021)
The purpose of this study is to determine the impact of Covid-19 on business performance of Starbucks. Plenty research of the impact of Covid-19 on the world economy has been done, but this research will focus more on the food and beverage industry, especially one of the famous brands called Starbucks. Qualitative and quantitative research methods such as online research and questionnaires were carried out to ensure the evaluation of the research is fresh, valid and reliable. It is assumed that the impact of Covid-19 has influence the Starbucks financially, economically and socially, which includes the behaviour of consumers towards the company. However, Starbucks was able to remain optimistic and position itself well to overcome the pandemic crisis.